2008
DOI: 10.1007/s10228-007-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use patterns of fishes across the mangrove-seagrass-coral reef seascape at Ishigaki Island, southern Japan

Abstract: To clarify seascape-scale habitat use patterns of fishes in the Ryukyu Islands (southern Japan), visual censuses were conducted in the mangrove estuary, sand area, seagrass bed, coral rubble area, branching coral area on the reef flat, and tabular coral area on the outer reef slope at Ishigaki . During the study period a total of 319 species were observed. Species richness and abundance were highest in the branching and tabular coral areas, followed in order by the seagrass bed and mangrove estuary, and coral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 30 publications
4
44
0
1
Order By: Relevance
“…(4) Do L. fulvus use mangroves as a nursery? The stomach contents and isotopic signatures of several sizes of 2 other species of snappers, humpback red snapper L. gibbus and mangrove red snapper L. argentimaculatus, were also investigated (as habitat control fishes), the former residing on coral reefs during the juvenile and adult life stages (control species for coral reef habitat), and the latter inhabiting mangroves until the body length reaches around 300 mm TL (control species for mangrove habitat; Shibuno et al 2008).…”
Section: Abstract: Mangrove · Coral Reef · Lutjanidae · Stable Isotomentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Do L. fulvus use mangroves as a nursery? The stomach contents and isotopic signatures of several sizes of 2 other species of snappers, humpback red snapper L. gibbus and mangrove red snapper L. argentimaculatus, were also investigated (as habitat control fishes), the former residing on coral reefs during the juvenile and adult life stages (control species for coral reef habitat), and the latter inhabiting mangroves until the body length reaches around 300 mm TL (control species for mangrove habitat; Shibuno et al 2008).…”
Section: Abstract: Mangrove · Coral Reef · Lutjanidae · Stable Isotomentioning
confidence: 99%
“…At Ishigaki Island, southern Japan, Shibuno et al (2008) found that juvenile L. fulvus (30 to 120 mm in total length, TL) predominantly occurred in mangrove estuaries but sometimes occurred over reef flats, while subadults and adults (>120 mm TL) inhabited coral reefs, based on a quantitative visual census across multiple habitats (mangrove estuary, sand area, seagrass bed, coral rubble area, branching coral area on the reef flat, and tabular coral area on the reef slope). During the daytime, L. fulvus swim actively within each habitat, while at night they are found around mangrove prop roots, rocks on river bottoms, or under corals.…”
Section: Abstract: Mangrove · Coral Reef · Lutjanidae · Stable Isotomentioning
confidence: 99%
“…Rhizophora stylosa, Bruguiera gymnorrhiza, Kandelia candel, and Lumnitzera racemose dominate the mangrove forest. In the center of the river mouth, the water depth ranges from 0.5 to 1 m at low tide and 1 to 2 m at high tide, where mangrove prop roots are alternately inundated and exposed, during the tidal cycle Shibuno et al, 2008). The seagrass bed (water depth range of 0.5-1 m at low tide and 2-3 m at high tide) extends for about 2.5 km along the coast at a distance of 30 to 120 m offshore, and is dominated by Thalassia hemprichii .…”
Section: Study Areamentioning
confidence: 99%
“…Juvenile stage Lutjanus sp. are relatively small (around 30-125 cm) Shibuno et al, 2008), and they inhabit MG as a nursery. Juvenile Lutjanus sp.…”
Section: Proportional Contribution Of Dz In the Diet Of Consumersmentioning
confidence: 99%
“…Lethrinus spp. predominantly inhabit back-reef seagrass beds at the juvenile life stage (Wilson 1998, Nakamura & Tsuchiya 2008, Shibuno et al 2008, thereby utilizing the beds as a potential nursery habitat that produces relatively more adult recruits per unit area than other juvenile habitats (Beck et al 2001). Afterwards, juveniles move to coral reef habitats at maturity, and adults often form large aggregations for pelagic spawning at outer reefs.…”
Section: Introductionmentioning
confidence: 99%